Crisis in the Mediterranean neighbourhood: A test for the European union migration policy - Stojanović Nikola (Međunarodni Problemi, 2015)
The paper analyses the implementation of the EU immigration and asylum policy and the control of EU member states' external borders in the aftermath of the Arab Spring. The author argues that the European Union pursues an exclusive version of those policies aimed at reducing the immigration pressure as well as preventing illegal border crossings into the member states. Two key mechanisms have been identified in the EU policy implementation: 1) a restrictive border control regime, and 2) agreements to transfer border management and supervision tasks to the third countries (transitional countries). The author emphasizes that the development of an exclusive migration strategy was not followed by the needed changes of the inclusive aspects of the EU immigration and asylum policy and the control of external borders; in fact, the EU member state's asylum systems were not preventively strengthened as to enhance national capacities to receive and integrate new migrants. The dramatic increase of the number of illegal crossings of the European Union external borders in 2014 caused the collapse of the EU immigration strategy, and failures in national asylum systems of the member states. The author concludes that partially integrated EU immigration and asylum policy at national level led to the dysfunctional external border management and the EU's loss of control over massive immigration influxes.